Eugenics and Historical Memory in America - Stern, Alexandra Minna (History compass, 2005)
How is the history of eugenics in America remembered, and forgotten? In this article, I explore the recent gubernatorial apologies for forced sterilizations, which were carried out under the authority of state eugenics laws from 1907 until the 1970s. I situate the apologies in the global context of movements for reparations and restitution, examine the discursive architecture of apologies that seek to address the contravention of medical ethics and trust, and suggest that the apologies have the potential to elide important aspects of the history of eugenics in America.